Social assistance and adaptation to flooding in Bangladesh - Ahmed, Akhter; Bakhtiar, M. Mehrab; Hidrobo, Melissa; Hoddinott, John F.; Mueller, Valerie; Quabili, Wahid; Rakshit, Deboleena; Roy, Shalini; Thiede, Brian (CGIAR System Organization, 2024)
As climate change exacerbates weather shocks, there is growing interest in understanding whether social assistance programs can support coping among poor rural households and whether program effects vary by gender. We assess whether a social assistance program – the Transfer Modality Research Initiative (TMRI) –influenced the effects of prior monsoon flooding on household consumption and adult diets in southern Bangladesh. TMRI provided cash or food transfers, with or without nutrition behavior change communication, from 2012-2014. Within the study sites and years, flooding was substantial but moderate. Our findings suggest that, without TMRI, a one-standard-deviation increase in lagged flooding led to households smoothing consumption by drawing down savings and reducing diet quality among both men and women. In contrast, among TMRI treatment households, lagged flooding did not reduce savings, and both men’s and women’s diet quality improved. Effects on diet quality appeared largely driven by legumes and by fruits and vegetables, and improvements appeared strongest among households receiving both transfers and behavior change communication. Results indicate that social assistance can help households cope with effects of moderate flooding in southern Bangladesh, protecting household savings and improving both men’s and women’s diets.